2011
DOI: 10.4103/0972-5229.84896
|View full text |Cite
|
Sign up to set email alerts
|

Dengue encephalitis

Abstract: We report a case of dengue fever with features of encephalitis. The diagnosis of dengue was confirmed by the serum antibodies to dengue and the presence of a dengue antigen in the cerebrospinal fluid. This patient had characteristic magnetic resonance imaging brain findings, mainly involving the bilateral thalami, with hemorrhage. Dengue is not primarily a neurotropic virus and encephalopathy is a common finding in Dengue. Hence various other etiological possibilities were considered before concluding this as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 7 publications
1
32
0
1
Order By: Relevance
“…Borawake K et al, reported a case of dengue encephalitis. 12 Dengue cerebellitis was seen in 2.83% of cases in present study. Withana M et al reported one case of dengue cerebellitis.…”
mentioning
confidence: 42%
“…Borawake K et al, reported a case of dengue encephalitis. 12 Dengue cerebellitis was seen in 2.83% of cases in present study. Withana M et al reported one case of dengue cerebellitis.…”
mentioning
confidence: 42%
“…Borawake et al reported a case of DE that had MRI findings suggestive of lesions in bilateral thalamus, pons and cerebellar regions [7]. These findings are more sensitive in cases of Japanese encephalitis [8].…”
Section: Discussionmentioning
confidence: 85%
“…Dengue virus, classically labeled as a nonneurotropic virus [3], is associated with numerous rare neurological manifestations of dengue infection such as transverse myelitis, Guillain-Barré syndrome, acute disseminated encephalomyelitis, and myositis [4,5]. Dengue encephalopathy is now a well-recognized, though uncommon, entity with incidence ranging from 0.5% to 6.2% [6].…”
Section: Discussionmentioning
confidence: 99%